New Product Demand Forecasting and Inventory Model Towards Eyewear Cleanser Product: A Case Study of Nasho Company (Journal of Innovation, Business and Entrepreneurship, 2020)
Nasho Company is Nano-coating business based on chemicals. This business makes a product called "Nasho Self-cleaning liquid for Glasses" that give self-cleaning ability for glasses surface. This Company desires to do market expansion by putting the product in local optical stores in Bandung. Yet, the targeted that they already made need to be cross-checked.  On another hand, the productivity and efficiency of production in this Company are low due to order the material and produce the product only when demand comes. Production planning based on forecasting and inventory model is required for solving this problem. As a result, the Company could define market expansion target as well as material stocking. This research is using Structured Analogy Forecasting to define the forecast for new product and Fixed Order Interval with Safety Stock for material stocking. Mix method is used in this research to gain information and identify the product that would be a benchmark in forecasting technique that in line with Inventory Model analysis. As a result of Structured Analogy forecasting, the benchmark product is Expo lenses cleaner using the judgmental process with thematic analysis and Single Exponential Smoothing with ?= 1,92215 is applied with MAPE 6,42%, MAD= 59,68, and MSD= 5362,4, as well as demand in next year, would be 10631 bottles of lenses cleaner liquid. By 95% service level for Fixed Order Interval with Safety Stock, the Company would order; 14 l of Ethanol, 2,5 l Polydimethylsiloxane, 2 l of Isopropyl, 870 unit of the bottle, 13 boxes of wiper, 207 A3+ sheets of box, 25 A3+ sheets of the sticker, and 47 sheets of 1 m HVS of Instruction Paper in every 14 working days.Keywords:  Nano-coating, Self-cleaning for glasses, Structured Analogy Forecasting, Inventory Model, Mix Method.